Influence of the Administrators’ Decisiveness Competency on Provision of Quality Education in Kitutu Central Sub-County, Kenya - Grace Getonto; Dr. Charles Ocharo Momanyi (IJRDO- Journal of Educational Research, 2020)
Leadership in education plays a very important role of change in society and for this to happen, effective leaders are critical. The purpose of the study was to assess the school administrators’ competencies on the provision of quality education in public secondary schools in kitutu central sub-county. The study aimed at: assessing the school administrators’ level of competence on, establishing school administrators’ level of training, assessing how school administrators’ mobilize resources’ on quality education in Kitutu Central Sub- County. This study was anchored on transformational leadership theory and Contingency theory. This study employed mixed methods approach and concurrent triangulation design was adopted which included both qualitative and quantitative data analysis. The target population in this study comprised of 7568 respondents who included: 22 principals in Kitutu Central Sub-county, 500 teachers, 7046 students and one Quality Assurance and Standards Officers in the SDE’s office. A total of 618 respondents were sampled comprising 19 Principals, using simple random sampling, 618 teachers and 382 students who were also sampled randomly and one QASO, who was sampled purposively. Data from respondents were collected using questionnaires derived from study objective and interviews guides. The questionnaires sought answers from teachers and students while interview guides from School administrators and QASO. Piloting of research instruments was carried out at Nyamache Sub- County on 10% of the sample size in order to pre-test the relevance and accuracy of the research instruments. Validity of instruments was tested using content validity through supervisors expertise while reliability of instruments was tested using test re-test technique and Cronbach’s alpha method of 0.75 was used to calculate the internal efficiency. Credibility of the data was tested using data triangulation through multiple analysis while dependability of data was assured through reporting data collection process in details. Qualitative data was analyzed in narrative form while quantitative data was coded and entered in to Statistical Package for Social Sciences (SPSS) version 23.0 to produce both descriptive and inferential statistics. Descriptive statistics were analyzed to find mean, mode and standard deviation while on the other hand inferential statistics was analyzed in form of correlation, regression and analysis of variance (ANOVA). and presented inform of frequencies, tables, graphs and charts in order to answer questions related to the research topic. The findings revealed that majority of the school administrators were competent in in enhancing quality education. It further revealed that majority of them had undergone a training course in either management and planning, administration and management, leadership and management. It also indicated a positive relationship between the school administrators’ resource mobilization and quality education. The study also revealed that school administrators motivational practices enhances staff development, enhances responsibility and recognition, improves teacher support and performance and facilitates general school performance. The study recommends an in-depth study to assess the of school principals competencies on the general management of secondary schools using a bigger sample and covering a wider geographical area